A Highly Selective Perylenediimide-Based Chemosensor: “Naked-Eye” Colorimetric and Fluorescent Turn-On Recognition for Al3+ - Liu, Yan; Gao, Shuang; Yang, Liu; Liu, Yu-Long; Liang, Xiao-Min; Ye, Fei; Fu, Ying (Frontiers in Chemistry, 2020)
A novel “turn-on” fluorescent probe (PCN) was designed, synthesized and characterized with perylene tetracarboxylic disimide as the fluorophore and Schiff base subunit as the metal ion receptor. The probe demonstrated a considerable fluorescence enhancement in the presence of Al3+ in DMF with high selectivity and sensitivity. Furthermore, the considerably ‘off-on’ fluorescence response simultaneously led to the apparent color change from colorless to brilliant yellow, which could also be identified by naked eye easily. The sensing capability of PCN to Al3+ was evaluated by the changes in UV-vis, fluorescence, FTIR 1H NMR and HRMS spectroscopy. The linear concentration ranges for Al3+ was 0-63 μM with detection limit of 0.16 μM, which allowed for the quantitative determination of Al3+.